HUBUNGAN KECEPATAN LARI 30 METER DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA KELAS VIII1 SMP 13 PEKANBARU - Yudha Rama Yulis P; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the author's observation at SMP 13 Pekanbaru, athletic learning has not been implemented properly, especially long jump. This is from the results of data or direct observation of the long jump which is still unsatisfactory (low), especially in the proven squatting force. The purpose of this study was to see a significant relationship between running speed of 30 meters and the results of long jump squatting in class VIII1 SMP 13 Pekanbaru. The population of this study were all students of class VIII1 who took lessons in accordance with 72 people, namely 30 male students and 42 female students (data source: data of physical education teachers at SMP 13 Pekanbaru in 2018). Sampling in this study using purposive sampling, so that the sample in this study only for men who can be 30 people. The research instrument used a 30 meter run and long jump results. The results obtained in the ith analysis are simple. Based on the results of research and data processing using the research statistical system, it can be rejected that the relationship between the variable x and the y variable is obtained by the value of r = 0.541, then rxy> r table, namely (0.541> 0.367), then Ha is accepted. Conclusion The hypothesis is accepted at a significant level = 0.05, in other words, there is a significant relationship between the 30 meter running speed and the long jump result of the squat style in class VIII1 students of SMP 13 Pekanbaru.Key Words: 30 Meter Run, Long Jump Results